Record of two Late-Holocene tsunamis along the north Peruvian coast and their relation to archaeological sites of the Chicama River valley - Goodbred, Steven L; Dillehay, Tom D (Holocene (Sevenoaks), 2025)
South America’s Pacific margin is subject to recurring subduction-zone earthquakes that have generated devastating historical tsunamis, as well as earlier events impacting indigenous populations that have lived along the region’s rich upwelling coastlines throughout the Holocene. Despite recurring events, the geologic record of paleo-tsunamis is relatively sparse. Here we report evidence for two paleo-tsunamis striking the Chicama River coastline (8°S) around 2.8 and 2.0 ka. The two sedimentary deposits are amalgamated in many locations and can be difficult to distinguish, but floodplain or shoreface deposits separate the two units when traced landward and seaward, respectively. The magnitude of each event was sufficient to erode coarse cobbles (13–25 cm) from the shoreface and transport them ~100 m before being deposited as rapidly thinning and fining gravel units. Based on the distribution of mobilized cobbles, we consider plausible flow characteristics for the two tsunamis suggesting that each was on the order of at least a few meters in height with most of the cobble transport occurring only under critical to supercritical flow at the wave front. Previous archaeological reports from the area correctly recognized the older tsunami event but did not describe the younger, better-preserved second event. Further, we revisit the archaeological evidence for the tsunami and recast the older event as likely being more moderate than previously suggested. Broader archaeological evidence from this 30-km reach of the Chicama valley shoreline also suggests that the late Cupisnique to Salinar and Gallinazo cultures were not severely disrupted by the tsunamis, even with these events undoubtedly impacting nearshore inhabitants at the time.